p(x) = x^3 + 0x^2 - 28x - 48.

-4 | 1 | 0 | -28 | -48 | | -4 | 16 | -48 ----------------------------- 1 -4 -12 0

I.e. p(x) = (x+4)*(x^2 - 4x -12). To find remaining zeros we have to solvex^2 - 4x - 12 = 0, a quadratic equation. Use the simplified formula for even b:

x2,3 = 2 +- sqrt(4+12) = 2 +- 4,so x2 = -2, x3 = 6.

Zeros: -4, -2, 6.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up